2020
DOI: 10.1073/pnas.2012150117
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-oriented profiling of autoinhibitory kinase conformations predicts RAF inhibitor efficacies

Abstract: Kinase-targeted therapies have the potential to improve the survival of patients with cancer. However, the cancer-specific spectrum of kinase alterations exhibits distinct functional properties and requires mutation-oriented drug treatments. Besides post-translational modifications and diverse intermolecular interactions of kinases, it is the distinct disease mutation which reshapes full-length kinase conformations, affecting their activity. Oncokinase mutation profiles differ between cancer types, as it was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 73 publications
(141 reference statements)
0
52
0
Order By: Relevance
“…The full sets of predictions are included in the supplementary tables S4-S7. To validate R esistor ’s predictions, we compared its predictions with two sources of experimental data: a saturation mutagenesis variant effect assay from Wagenaar et al [61] and a cell-based kinase conformation reporter assay termed KinCon by Stefan and colleagues [62, 63]. Furthermore we carried out new KinCon experiments on a number of R esistor predictions to validate R esistor ’s predictive capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The full sets of predictions are included in the supplementary tables S4-S7. To validate R esistor ’s predictions, we compared its predictions with two sources of experimental data: a saturation mutagenesis variant effect assay from Wagenaar et al [61] and a cell-based kinase conformation reporter assay termed KinCon by Stefan and colleagues [62, 63]. Furthermore we carried out new KinCon experiments on a number of R esistor predictions to validate R esistor ’s predictive capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…KinCon reporter: Following PCR amplification of the human MEK1 gene (MEK1: NM_002755.3), we fused it N-terminally with -F[1] and C-terminally with -F[2] of the R luc -PCA (pcDNA3.1 backbone vector) as previously described [ 27 , 28 ]. We inserted interjacent 10-aa standard linkers as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…This kinase conformation reporter system, which we have named KinCon, can be extended to a collection of full-length kinases for tracking their different kinase activity states [ 26 ]. In the proof-of-concept studies, we have shown that the engineered luciferase-based biosensors can be used to systematically track mutation and drug-driven changes of RAF kinase conformations in intact cell settings [ 26 , 27 , 28 ]. It is of interest that MEK kinases are smaller in size, when compared to RAF, but still they contain a N-terminal “negative regulatory region” which participates in stabilizing an inactive kinase conformation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it is of interest that many kinases share a similar concept for kinase regulation. This involves so-called intramolecularly acting cis-regulatory elements (CREs) or auto-inhibitory modules (AIM) which control substrate access and kinase activity states [30][31][32][33]. The kinase OFF state is characterized by interaction and association of the CRE with the catalytic cleft of the kinase domain.…”
Section: Personalized Medicinementioning
confidence: 99%